Cancer-related vulnerable lesions in patients with stable coronary artery disease. (15th July 2021) - Taruya, Akira; Nakajima, Yuki; Tanaka, Atsushi; Kashiwagi, Manabu; Tanimoto, Takashi; Kuroi, Akio; Shiono, Yasutsugu; Shimamura, Kunihiro; Kubo, Takashi; Sougawa, Hiromichi; Masuno, Tomizo; Ozaki, Yuichi; et al.
Abstract: Background: Coronary artery disease (CAD) has become a major cause of morbidity and mortality in cancer survivors. It is still unclear whether cancer history influences lesion characteristics. The purpose of this study was to investigate cancer-related lesion morphology in patients with CAD. Methods: This study enrolled 400 patients with stable CAD. The patients were classified into a cancer survivor group ( n  = 69) and a noncancer group ( n  = 331). We investigated coronary lesion morphology by optical coherence tomography, and we assessed the prognosis in terms of both all-cause mortality and major adverse cardiovascular events (MACE). Results: Adenocarcinoma was the most common histopathological diagnosis. Serum C-reactive protein levels were significantly higher in the cancer survivor group than in the noncancer group (cancer survivors 0.12 [0.05–0.42] mg/dL vs. noncancer 0.08 [0.04–0.17] mg/dL, p  = 0.019). The cancer survivor group was more likely than the noncancer group to have thrombi (cancer survivors 30.4% vs. noncancer 15.4%, p  = 0.004), and layered fibrotic plaques (LFPs; cancer survivors 18.8% vs. noncancer 3.6%, p  < 0.0001). Cancer survivors had poorer outcomes than noncancer controls in terms of both all-cause mortality ( p  = 0.020) and MACE ( p  = 0.036). Conclusions: Because of underlying inflammation, CAD patients with cancer had more high-risk lesions than those without cancer, which could result in poorer prognosis for the former. This result might inform the management of CAD in cancer patients in terms of secondary prevention. Highlights: Coronary artery disease (CAD) patients with cancer had more high-risk coronary lesions than CAD patients without cancer. The serum CRP levels of CAD patients with cancer were higher than those without cancer. The prognosis of CAD after percutaneous coronary intervention was worse in patients with cancer than in those without.